2005
DOI: 10.1124/mol.104.008292
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Kir2 Inward-Rectifier Potassium Channels to a Mitochondrial Uncoupler: Identification of a Regulatory Site

Abstract: The aim of this study was to gain insight into the mechanism by which members of the K ir 2 subfamily are differentially sensitive to agents that inhibit mitochondrial function by identifying responsible site(s) in K ir 2 proteins. K ir 2 channels were expressed in Xenopus laevis oocytes and assayed by two-electrode voltage clamp and patch clamp. Incubation of oocytes in carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP), a mitochondrial uncoupler,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Further, upregulation of I K1 may have stabilizing effects on ventricular tachyarrythmias [8]. Conversely, Kir2 channels may provide a functional link between mitochondrial dysfunction and membrane excitability [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Further, upregulation of I K1 may have stabilizing effects on ventricular tachyarrythmias [8]. Conversely, Kir2 channels may provide a functional link between mitochondrial dysfunction and membrane excitability [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported an increase in K ir 2 channel activity in excised, inside-out membrane patches from oocytes pre-treated with FCCP (Collins et al, 2005). In the present study we took a closer look at this apparent recovery from FCCP because the conditions required for recovery could provide important clues to the mechanism.…”
Section: Mechanism Of Recovery From Fccpmentioning
confidence: 67%
“…In a previous study we found that the sensitivity of K ir 2 channels to FCCP was influenced by mutations that are known to alter PIP 2 sensitivity (Collins et al, 2005). This raised the possibility that FCCP inhibits K ir 2 channels by PIP 2 depletion.…”
Section: Evidence For An Endogenous Inhibitormentioning
confidence: 97%
See 2 more Smart Citations